2017
DOI: 10.1112/s0010437x17007072
|View full text |Cite
|
Sign up to set email alerts
|

Vinogradov’s three primes theorem with almost twin primes

Abstract: Abstract. In this paper we prove two results concerning Vinogradov's three primes theorem with primes that can be called almost twin primes. First, for any m, every sufficiently large odd integer N can be written as a sum of three primes p 1 , p 2 and p 3 such that, for each i ∈ {1, 2, 3}, the interval [p i , p i + H] contains at least m primes, for some H = H(m). Second, every sufficiently large integer N ≡ 3 (mod 6) can be written as a sum of three primes p 1 , p 2 and p 3 such that, for each i ∈ {1, 2, 3}, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…Bearing in mind Chen's result, one may try to study the arithmetical properties of the set of primes p such that p + 2 ∈ P r for a fixed r ≥ 2 and, in particular, to establish the solvability of diophantine equations or inequalities in such primes. For example, Matomäki and Shao [11], improving author's results from [17] and [18] as well as a result of Matomäki [10], proved that every sufficiently large odd integer N can be represented as a sum ot three primes p 1 , p 2 , p 3 such that p i + 2 ∈ P 2 , i = 1, 2, 3. Other results of this type were found by the author [19], and by Dimitrov and Todorova [6].…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…Bearing in mind Chen's result, one may try to study the arithmetical properties of the set of primes p such that p + 2 ∈ P r for a fixed r ≥ 2 and, in particular, to establish the solvability of diophantine equations or inequalities in such primes. For example, Matomäki and Shao [11], improving author's results from [17] and [18] as well as a result of Matomäki [10], proved that every sufficiently large odd integer N can be represented as a sum ot three primes p 1 , p 2 , p 3 such that p i + 2 ∈ P 2 , i = 1, 2, 3. Other results of this type were found by the author [19], and by Dimitrov and Todorova [6].…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…Up to now many hybrid theorems were proved. One of the best result belongs to K. Matomäki and Shao [8]. They proved that every sufficiently large odd integer n such that n ≡ 3 (mod 6) can be represented as a sum n = p 1 + p 2 + p 3 of primes p 1 , p 2 , p 3 such that…”
mentioning
confidence: 99%
“…In 2000 Tolev [12] proved that for every sufficiently large integer N ≡ 3 (mod 6) the equation (1) has a solution in prime numbers p 1 , p 2 , p 3 such that p 1 + 2 ∈ P 2 , p 2 + 2 ∈ P 5 , p 3 + 2 ∈ P 7 . Thereafter this result was improved by Matomäki and Shao [8], who showed that for every sufficiently large integer N ≡ 3 (mod 6) the equation (1) has a solution in prime numbers p 1 , p 2 , p 3 such that p 1 + 2, p 2 + 2, p 3 + 2 ∈ P 2 .…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…Suppose that D, ∆ are define by(10) and ξ, δ are specified by (41). Suppose also that λ(d) satisfy (25) and c m are define by(8).X 1− c 4 ∆ − 1 4…”
mentioning
confidence: 99%